Physicochemical characteristics of non-starch polysaccharides extracted from cassava tubers - Uthumporn U.,; Nadiah I.,; Izzuddin I.,; Cheng, L.H.; Aida H., (Penerbit Universiti Kebangsaan Malaysia, 2017)
This research mainly focused on isolation of non-starch polysaccharide (NSP) from different parts of cassava tuber by using water extraction and to evaluate the effect of NSP addition into flour on nutritional composition, swelling and solubility, pasting properties and dough characteristics by farinograph and extensograph. Three origins of (NSP) extracted were used: cassava peels, coarse and fine portions from cassava flesh. The isolation of NSP was done by using water extraction method and designated as water-extractable (WEP) and water un-extractable non starch polysaccharides (WUP). The percentage yield of WEP (0.24 - 1.64%) from water extraction was significantly lower as compared to WUP (2.58 - 4.33%). Upon the incorporation of 5% NSP, the cassava flour showed lower moisture content compared to the sample without the addition of NSP, while fats and crude fiber content of cassava flours were found to be increased upon the incorporation of 5% NSP from all origins. Swelling power and solubility of cassava flour were being reduced upon the incorporation of 5% of NSP from cassava peel and coarse portion of cassava flesh. The changes in dough characteristics showed that water absorption of the samples upon the addition of 5% NSP into wheat flour was found to be higher compared to control wheat flour. In contrast, dough stability and extensibility, tolerance index, resistance to extension, as well as the work input necessary for dough deformation from wheat flour with addition of 5% NSP resulted lower than control wheat flour. Overall, NSP extracted from cassava peels and coarse portion of cassava flesh performed similar characteristics and functional properties upon the incorporation into the flour.